The Influence of Hedonic Motivation on Online Purchase Intention: The Mediating Role of Information Availability Among University Student in Bandung - Duki, Ahmad Zufar Aptawangsa; Namuri, Diana Sari; Hartadi, Adhi Prapaskah (Universitas Muhammadiyah Sorong, 2026)
This study aims to examine the effect of hedonic motivation on online purchase intention (OPI) among university students in Bandung who represent a large segment of digital natives, while also analyzing the mediating role of information availability. Data were collected through an online questionnaire consisting of 18 indicators and obtained 228 valid responses. The analysis was conducted using Partial Least Squares Structural Equation Modeling with SmartPLS 4. The results of the measurement model confirmed that all constructs met the requirements for convergent validity, discriminant validity, and reliability. Among the dimensions of hedonic motivation, gratification shopping emerged as the strongest predictor, while social shopping showed weaker influence. These findings highlight the importance of emotional satisfaction and enjoyable shopping experiences in shaping students’ online purchase behavior. This study contributes to the literature on digital consumer behavior and provides practical implications for e-commerce platforms to strengthen hedonic values, particularly through strategies that integrate social interaction to increase purchase intention among young consumers. Future research is encouraged to include other constructs such as utilitarian motivation, e-service quality, and electronic word of mouth, as well as broader samples to improve external validity.